Durability performance of Gigantochloa scortechinii through Laboratory fungal decay tests - Razak Wahab; Mahmud Sudin; T. Mustapa; Awang Ahmad Yunus (Academic Journals Inc., 2006)
Durability performance of chemically treated bamboo Gigantochloa scortechinii were evaluated through laboratory fungal tests. Soft rot and white rot caused high weight loss to G. scortechinii in the monoculture decay tests. The 2 year-old G. scortechinii are more susceptible than the 4 year-old to the attack of soft, white and brown rot. Vacuum pressure treated blocks shows the best performance against decaying fungi. This is followed by soaking treated blocks. CCA and ACQ shows good resistance against decaying fungi with CCA performing slightly better than the ACQ. The 4% chemicals solution strength were found to be sufficient in controlling the decaying fungi. Similar results were observed in the pattern attack of soft rot in the monoculture tests